Polyphonies and research horizons for the Colombian Applied Linguistics Journal - Castañeda-Peña, Harold (Colombian Applied Linguistics Journal, 2014)
Welcome to our Colombian Applied Linguistics Journal new issue. The present journal edition proposes a hermeneutical exercise on domains of applied linguistics inviting readers to be “implied” revisiting and renewing research horizons at national and international levels around three research interests: Education and professional development of language teachers, Literacy processes and new literacies in two languages and Discourse studies in educational contexts. These academic paths are also the foci of our graduate programme in Applied Linguistics to TEFL at Universidad Distrital Francisco José de Caldas, and they constitute our own research agenda.